تحسين عملية التعرف على إشارات المرور باستخدام التعلم العميق باعتماد على شبكة SqueezeNet - حسين ماجدولين عبد المجيد (Latakia University Journal -Engineering Sciences Series, 2019)
Artificial Intelligence(AI) and Machine Learning(ML) are some of the hottest topics right now. Once you’ve read this article, you will understand the basics of AI and ML,the most important branch of Machine Learning is Deep Learning(DL). There are lots of applications about Deep Learning, now we will discuss Recognizing of Traffic Lights state in any photo taken by Nexar application. We were compelled to explain extra conceptions from Image Processing such image rotation and day and night separating. [2,3] All researches depend on the model accuracy and model size with MB,where the smallest model take the higher score. Using of many models and intersecting the results improve the accuracy, so we have used the models reassembling.At the end,we get a model with accuracy 94.83% and model size 7.84MB Whereas the model accuracy on Nexar samples was 94.955%. SqueezeNet has been relying on smaller models as well as having pre-trained models using Image Net. أصبح مصطلح الذكاء الصنعي وتعلم الآلة أكثر المواضيع المتداولة في وقتنا الحالي، يساهم هذا البحث بتعليم أساسيات الذكاء الصنعي وتعلم الآلة والشيء الأكثر أهمية أن تعرف أن التعلم العميق يعتمد على تدريب الشبكات العصبية في أحد شكلي التدريب بإشراف أو بدون إشراف. هناك تطبيقات هائلة للتعلم العميق، نركز في هذا البحث على التعرف على حالة إشارة المرور في أي صورة مأخوذة عن طريق تطبيق نيكسار. وكان لابد من الاستعانة ببعض المفاهيم من مجال معالجة الصورة كشرح تدوير الصور وفصل الليل و النهار عن طريق فحص معدل كثافة البكسل [2,3]. جميع الأبحاث تركز على دقة النموذج بالتوازي مع حجم النموذج بالميغابايت حيث النموذج الأصغر يأخذ الدرجات الأعلى. إن استخدام عدة نماذج مع بعضها البعض و مقاطعة النتائج يحسن الدقة بشكل جيد، لذا استخدمنا تقنية تجميع النماذج حيث حصلنا على دقة النموذج على عينات الصلاحية كانت 94.83%, بحجم نموذج 7.84 ميغابايت حيث أن دقة النموذج على عينات اختبار نيكسار هي. 94.955% تم الاعتماد على شبكة SqueezeNet كونها تعتمد نماذج أقل إضافة إلى امتلاكها نماذج مدربة مسبقا باستخدام Image Net.